2000
DOI: 10.1128/iai.68.11.6257-6264.2000
|View full text |Cite
|
Sign up to set email alerts
|

Human Neutrophil-Mediated Nonoxidative Antifungal Activity againstCryptococcus neoformans

Abstract: It has long been appreciated that polymorphonuclear leukocytes (PMN) kill Cryptococcus neoformans, at least in part via generation of fungicidal oxidants. The aim of this study was to examine the contribution of nonoxidative mechanisms to the inhibition and killing of C. neoformans. Treatment of human PMN with inhibitors and scavengers of respiratory burst oxidants only partially reversed anticryptococcal activity, suggesting that both oxidative and nonoxidative mechanisms were operative. To define the mediato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 60 publications
(52 reference statements)
2
75
0
Order By: Relevance
“…S100 proteins are calcium-binding cytosolic proteins that can be expressed by multiple cell types, including alveolar epithelial cells, endothelial cells, monocytes, macrophages, neutrophils and dendritic cells (DCs) (Ehrchen et al, 2009;Foell et al, 2007;Ramirez-Ortiz et al, 2011). Importantly, calprotectin may have direct antifungal and fungistatic activity against fungi, including C. neoformans (Mambula et al, 2000;McCormick et al, 2010;Urban et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…S100 proteins are calcium-binding cytosolic proteins that can be expressed by multiple cell types, including alveolar epithelial cells, endothelial cells, monocytes, macrophages, neutrophils and dendritic cells (DCs) (Ehrchen et al, 2009;Foell et al, 2007;Ramirez-Ortiz et al, 2011). Importantly, calprotectin may have direct antifungal and fungistatic activity against fungi, including C. neoformans (Mambula et al, 2000;McCormick et al, 2010;Urban et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Together, these activities indicate a putative role in regulating leukocyte migration to inflammatory sites. S100A8/A9 is also known to inhibit microbial growth, presumably by chelating zinc (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and to inhibit bacterial adhesion to mucosal epithelial cells (34). Thus, it is reasonable to propose a role in innate immune responses to bacterial infections for these molecules.…”
mentioning
confidence: 99%
“…For instance, the protein beta defensin-1 (BD1) and Cathelicidin (LL-37) peptide shows constitutive expression in the urinary tract, as both molecules from previous studies have demonstrated to play key roles in UTI's mitigation (Mambula et al, 2000;Chromek et al, 2006). Also, in a study of uncomplicated UTI subject, elevated level of LL-37 was observed (Nielsen et al, 2014), whilst E. coli isolates from healthy controls exhibited more susceptibility to LL-37 than isolates from UTI patients.…”
Section: Discussionmentioning
confidence: 94%
“…Also, in a study of uncomplicated UTI subject, elevated level of LL-37 was observed (Nielsen et al, 2014), whilst E. coli isolates from healthy controls exhibited more susceptibility to LL-37 than isolates from UTI patients. Further, BD1 has also exhibited constitutive expression in the urinary tract and hence, BD1 is suggested to play a role in pyelonephritis (Smith et al, 2011;Mambula et al, 2000;Morrison et al, 2002) and act as a defence against Gram-positive uropathogens (Morrison et al, 2002). Moreover, studies on defensins (Mambula et al, 2000), contained in neutrophil granules, indicated antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation